GxE effects on Tocopherol composition of oils from very old and genetically diverse olive trees - Rodrigues, Nuno (2018)
Tocopherols are compounds with high biological activity, beneficial for human health that can be found in vegetable oils like olive oil, contributing for its resistance to oxidation. In this work, the tocopherol contents of olive oils extracted from centenarian olive trees of six cultivars (cvs. Lentisca, Madural, Rebol~a, Redondal, Verdeal, and Verdeal Transmontana) were evaluated during five consecutive crop seasons (2013–2017). Three tocopherol isoforms (α-, β- and γ-tocopherols) were detected in all analyzed olive oils, and their content varied significantly with the cultivar and year of production. The highest amounts were found in cv. Lentisca (456 122 mg/kg olive oil), while the lowest were observed in cv. Verdeal (179 45 mg/kg olive oil). Crop year was the most influential factor, with the highest contents observed in 2013 and lowest in 2014. Principal component analysis and hierarchical clustering analysis helped differentiate olive oils according to cultivar or production year. These data suggest that tocopherol composition may serve as a chemical marker to distinguish the subject cultivar olive oils from centenarian trees either by olive cultivar or by crop year, being some cultivars identified as potential candidates for guaranteeing the production of olive oils rich in these compounds.